Consumption of submerged aquatic macrophytes by rudd (Scardinius erythrophthalmus L.) in New Zealand - Lake, M. D.; Hicks, B. J.; Wells, R. D. S.; Dugdale, T. M. (Hydrobiologia, 2002)
In experiments in New Zealand, rudd (Scardinius erythrophthalmus L.) of 108-277 mm fork length (FL) ate a wide range of native and introduced submerged aquatic macrophytes in captivity and in the field. Rudd consumed the native charophytes Chara globularis Thuill., Chara fibrosa Ag. ex Bruz., and Nitella spp., the native macrophytes Potamogeton ochreatus Raoul. and Myriophyllum propinquum A. Cunn., and the introduced macrophytes Elodea canadensis Michx., Egeria densa Planch., Lagarosiphon major L., and Ceratophyllum demersum L. Rudd consistently consumed the Nitella spp. and Potamogeton ochreatus before Ceratophyllum demersum. From the results of experiments in tanks and in the field, we found the order of highest to lowest palatability was: Nitella spp. > Potamogeton ochreatus > Elodea canadensis> Chara globularis = Chara fibrosa> Egeria densa = Lagarosiphon major > Myriophyllum propinquum > Ceratophyllum demersum. The order of consumption was subject to some variation with season, especially for Egeria densa, Lagarosiphon major, and Myriophyllum propinquum. Rudd consumed up to 20% of their body weight per day of Egeria densa in spring, and 22% of their body weight per day of Nitella spp. in summer. Consumption rates were considerably lower in winter than in summer. The results of our field trial suggested that the order of consumption also applies in the field and that rudd are having a profound impact on vulnerable native aquatic plant communities in New Zealand. Nitella spp. and Potamogeton ochreatus are likely to be selectively eaten, and herbivory by rudd might prevent the re-establishment of these species in restoration efforts.[PUBLICATION ABSTRACT]